NGFR Increases the Chemosensitivity of Colorectal Cancer Cells by Enhancing the Apoptotic and Autophagic Effects of 5-fluorouracil via the Activation of S100A9 - Chen, Hao; Huang, Jintuan; Chen, Chunyu; Jiang, Yingming; Feng, Xingzhi; Liao, Yi; Yang, Zuli (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is currently the third leading cause of cancer-related deaths worldwide, and 5-fluorouracil (5-FU)-based chemotherapies serve as important adjuvant therapies before and after surgery for CRC. However, the efficacy of CRC chemotherapy is limited by chemoresistance, and therefore the discovery of novel markers to indicate chemosensitivity is essential. Nerve growth factor receptor (NGFR), a cell surface receptor, is involved in cell death and survival. Our previous study indicated that NGFR acts as a tumor suppressor, and high expression is associated with better outcomes in patients receiving 5-FU-based adjuvant chemotherapy after surgery. The aim of this study was to investigate the effect of NGFR on the chemotherapeutic response in CRC. Chemosensitivity was investigated using DLD1 and HCT8 cells after NGFR transfection. Apoptosis was investigated by flow cytometry. Autophagy was assessed using GFP-LC3B transient transfection. Gene expression was measured using an mRNA microarray. Beclin-1 and Bcl-2 protein expressions were assessed by western blot. NGFR and S100 calcium-binding protein A9 (S100A9) expressions in CRC patients were investigated by immunohistochemistry. The results showed that the half maximal inhibitory concentration of NGFR-transfected cells was lower than that of controls in DLD1 and HCT8 cells after 5-FU treatment, and cell viability was lower than in empty-vector cells. Tumor sizes were also smaller than in empty-vector cells in vivo. The percentages of apoptotic and autophagic cells were higher in NGFR-transfected cells. NGFR elevated the expression of S100A9 after 5-FU treatment. The combination of Bcl-2 and Beclin-1 was significantly suppressed by overexpressed NGFR. Five-year overall and disease-free survival in NGFR+/S100A9+ patients was better than in NGFR−/S100A9− patients. This study’s findings suggest that NGFR may serve as a marker predicting CRC patients’ chemosensitivity.